Предмет: Алгебра,
автор: malenkayalenni
Помогите решить:
1. (√5-1)^2 + (√3+1)^2
2. (√5-1)^2 - (2√5+1)^2
Ответы
Автор ответа:
0
Решение
1. (√5-1)^2 + (√3+1)^2 = 5 - 2√5 + 1 + 3 + 2√3 + 1 = 10 - 2(√5 - √3)
2. (√5-1)^2 - (2√5+1)^2 = 5 - 2√5 + 1 - 4*5 - 4√5 - 1 = - 15 - 6√5 = - 3(5 + 2√5)
1. (√5-1)^2 + (√3+1)^2 = 5 - 2√5 + 1 + 3 + 2√3 + 1 = 10 - 2(√5 - √3)
2. (√5-1)^2 - (2√5+1)^2 = 5 - 2√5 + 1 - 4*5 - 4√5 - 1 = - 15 - 6√5 = - 3(5 + 2√5)
Похожие вопросы
Предмет: Математика,
автор: Pavelhoney
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Литература,
автор: socarson151
Предмет: Химия,
автор: timotina76
Предмет: Геометрия,
автор: marlen12345